Beyond a Sustainable Consumption Behavior: What Post-pandemic World Do We Want to Live in? - Giannetti, Biagio F.; Fonseca, Tamara; Almeida, Cecília M. V. B.; Oliveira, José Hugo de; Valenti, Wagner C.; Agostinho, Feni (Frontiers in Sustainability, 2021)
The Covid-19 pandemic has uncovered the foremost struggles of the 21st century: social-economic inequality, global value chains, national security, and the environmental crisis. None of these seems novel, as many staged fiction dystopias have been predicting and warning mankind about the negative impacts of unsustainable consumption behaviors by displaying scenarios of exponential human population and economy growth. Several scientific tools for assessing sustainability have been developed to cover social, economic, and environmental aspects, however, most of them are simply used either separately or without a solid conceptual model supporting an epistemological construct to allow for deeper and scientific-based discussions on sustainability. This work presents a perspective about possible scenarios of the world’s sustainability, based on a straightforward integrated framework for its quantification. The three capitals of sustainability, summarized as environmental sustainability, productivity and happiness are combined, based on the input-state-output model, and further plotted on a 3-axis graph. Eight different combinations of the three capitals show eight potential future worlds. The least desirable scenario, named ‘Ineffective’, depicts an environmentally unsustainable, unhappy and poor world, whereas ‘Paradise’ is the utopia to be pursued: happy, environmentally sustainable and productive. Societies’ decisions on taking action after quantitatively measuring and monitoring sustainability will be determinant in placing the world on a more developed and sustainable path, and the model proposed in this work can be useful in promoting discussions in this direction.